Curriculum, human development and integral formation within the colombian caribbean - Álvaro Rodríguez Akle; Luis Alfredo González Monroy (Universidad del Magdalena, 2013)
This article describes the reality of the colombian Caribbean from the perspective of human development integral to start to understand that problematic situations are opportunities to enhance the transformations that allow to retrieve the subject social and collective. So the reconstruction of regional identity from the contributions of educational communities that build-oriented curriculum to become full, proactive, people with leadership and management capacity for sustainable development in a changing world. The article proposes some strategies to address alternatives to a society in which the quality of life and human dignity are the sense of the daily work in the context of the caribbean colombianidad and globalism in practice.